Pasa Ateh Traders' Strategies for Increasing Sales Amidst the Rise of Online Shops - Rila Purnama; Selvi Kasman; Yurisman (Kirana Publisher (KNPub), 2024)
This research discusses the strategies of market traders in increasing sales amidst the rise of online shops. The aim of this research is to explain the obstacles faced by PasaAteh traders amidst the proliferation of online shops as well as the strategies of PasaAteh traders in increasing their sales amidst the current proliferation of online shops. The research method used is qualitative research. Data collected through field observations, interviews and documentation. The theory used is Modernization Theory by Walt Rostow. The findings of this research are that market traders experience obstacles in increasing their business amidst the current rise of online shops. Online shops have had an impact on sales in the market. Technological advances have brought major changes in the marketing realm which has resulted in people preferring to shop online with all the convenience it offers, thus making market traders face obstacles in the form of intense competition, lack of promotion and marketing, changes in consumer habits, limited product availability and product variations. Therefore, market traders must maintain their business and create strategies by updating business models, loyalty and discount programs, improving customer service and increasing products and product variations.